2014
DOI: 10.1186/1471-2458-14-243
|View full text |Cite
|
Sign up to set email alerts
|

Large and forgotten in rural Australia: assessment, attitudes and possible approaches to losing weight in young adult males

Abstract: BackgroundYoung Adult Males (YAMs) in rural Australia are poorly studied with respect to overweight and obesity. Firstly, we explored the feasibility of recruiting 17–25 year old YAMs to obtain baseline data on overweight and obesity rates, socio-demographics, nutrition, exercise and mobile phone usage. Secondly, we explored the views of YAMs with a waist measurement over 94 cm about using mobile phone text messages to promote weight loss and incentives to promote healthy lifestyles.MethodsA two-staged, mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 23 publications
(35 reference statements)
4
22
0
2
Order By: Relevance
“…From a pragmatic perspective simply understanding the total yield from a recruitment strategy is insufficient [9]. Other factors are also salient such as the cost of recruitment and the representativeness of participants that are engaged through different recruitment strategies to ensure key subgroups in the population are not under-represented (e.g., those from lower SES, less educated, and minority groups [911]). This is not an insignificant point for those interested in eliminating health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…From a pragmatic perspective simply understanding the total yield from a recruitment strategy is insufficient [9]. Other factors are also salient such as the cost of recruitment and the representativeness of participants that are engaged through different recruitment strategies to ensure key subgroups in the population are not under-represented (e.g., those from lower SES, less educated, and minority groups [911]). This is not an insignificant point for those interested in eliminating health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…14 15 However, a qualitative UK study found high acceptance of body size among disadvantaged overweight/obese Scottish 13-14 years, 16 while qualitative US and Australian studies have found that adolescents recognise obesity as a societal issue, but not in themselves, and thus have low motivation to implement behavioural changes. [17][18][19] One reason why so little is known about how young adults view overweight/obesity or approach weight loss is that while it is relatively easy to study adolescents 'captive' in school or treatment programmes, they become largely invisible to researchers once they leave school. We have previously reported findings from a qualitative study of young adults nested within a large Scottish cohort study, where participants were well documented as having been overweight/obese in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…This revealed widespread recalled recognition of, but lack of major recalled concern about their overweight/obesity during adolescence, 20 consistent with other studies. [16][17][18][19] This data set also included reflections by participants on their lives since adolescence which have not so far been reported. Thus, this new qualitative analysis aimed to explore their transition to adulthood, by examining postschool weight-related concerns, behaviours and experiences related to young adult transitions among 24 year-olds categorised in terms of measured adolescent body mass index (BMI) trajectories and current BMI.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of multifaceted lifestyle interventions for prevention of weight gain to avert obesity has been established in young adult populations. However, the challenges of recruiting this target group to participate in weight management interventions have been well documented . Although there is limited research conducted to inform recruitment efforts for weight gain prevention interventions, some common challenges were recognized such as making initial contact, scheduling conflicts, lack of interest and unlikelihood to make any behaviour changes .…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited research conducted to inform recruitment efforts for weight gain prevention interventions, some common challenges were recognized such as making initial contact, scheduling conflicts, lack of interest and unlikelihood to make any behaviour changes . Some high risk subgroups among this life stage are even harder to recruit such as socioeconomically disadvantaged, less educated and ethnic minorities groups and males .…”
Section: Introductionmentioning
confidence: 99%